FAKTOR KOREKSI AKIBAT LEBAR JALUR JALAN TERHADAP LALU LINTAS RENCANA - Nono Nono (Direktorat Bina Teknik Jalan dan Jembatan, 2010)
Pavement design is determine of the type and pavement construction thicknesse to accomodate traffic for along design life. Estimation of traffic is very importance to the pavement design result.. Lane width is one from several problems wich impluence to estimation of design traffic, and lane width of road in Indonesia was varies and very different with foreign. Lane width of road can affect to riding confort and for road user safety, so road user behaviour will different depend on lane width of road is used. This paper discusses correction factos to design traffic effect of lane width, especially for road with two lanes two way. Activities undetaken are included literaure review, canalization survey or vehicle wheel path on several road links with two lanes two way with different lane width and data analysis.Based on the analysis result, found that for road with two lane two way and lane width is less than minimum lane width of 3.5 metres, so wheel path of vehicle wich use wheel path on design lane is more increase. Thus, for estimation of traffic in design lane is required correction factor. Especially for roads with fairly heavy volume, regional corners, climbs, or descendants, then the amount of lane width correction factor (fw) should be based on the survey results directly in the field.. Keywords: lane width of road,wheel path, design traffic, correction factor, two lane two way undivided.